Struktur Pasar dalam Pandangan Islam - Amin, Haris Al; Marliyah, Marliyah; Harianto, Syawal; Husna, Asmaul; Waqqosh, Abi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
Market structure in Islam is based on the principle of freedom, including in carrying out economic activities but is still limited by rules without neglecting the principles of responsibility and justice. Fair in this case is not detrimental to consumers or producers, related to producer surplus and consumer surplus. In Islam, Muslims are encouraged to try anything as long as they are still within the corridor of sharia, meaning that as long as the effort does not violate the provisions stipulated by Allah SWT. Likewise, in terms of carrying out economic activities, everything is permissible as long as it does not violate these rules. One of the economic activities can be seen in the market, where sellers and buyers meet to make transactions for goods or services, both in the form of production and pricing.